COMPLEX COACERVATION: A TECHNIQUE FOR ENCAPSULATION OF PROBIOTICS - Silva, Thaiane Marques da (2015)
Microencapsulation is the protection of a compound and modulation of its release and now, several techniques are available and among them there is the complex coacervation. The complex coacervation technique involves the association of two polymers and presents some advantages over other techniques such as the possibility of working with biopolymers, the absence of organic solvent and temperature conditions in mild processing. Functional foods containing probiotic bacteria are becoming increasingly popular in the market due to the beneficial health effects attributed to probiotics. However, these microorganisms are sensitive to various factors found in the environment that are exposed primarily to tratogastrointestinal and storage conditions. Thus, the microencapsulation is an alternative protection and controlled release for probiotics. However, factors such as temperature, pH and concentration of the hydrocolloid, particularly, can influence the formation of microcapsules. For the encapsulation of probiotics, although there are many related studies, however, according to these results, this technique can be regarded as promising for these microorganisms. Thus, this review article aims to address the key technological aspects related to microencapsulation of probiotics by the complex coacervation technique as well as the parameters related to the technique and its application potential.